Mobilizing Health Promotion Through Canada’s Student Mental Health Network: Concurrent, Mixed Methods Process Evaluation - Amy Ecclestone; Brooke Linden; Jessica Rose; Kiran Kullar (JMIR Formative Research)
Abstract BackgroundMental health issues among Canadian postsecondary students are prevalent. In tandem, an increased acknowledgment of the need for upstream mental health support has been highlighted. While the majority of institutions offer some form of mental health promotion, research suggests students are failing to access support due to barriers including lack of awareness, geographical and financial barriers, and lack of relevance in offerings. Canada’s Student Mental Health Network is a web-based knowledge mobilization initiative designed to fill these gaps. With content created and curated “for-students, by-students” and reviewed by subject matter experts, the Network serves as a one-stop shop for evidence-based, mental health support for postsecondary students. ObjectiveThe goal of this research was to conduct the first component of a comprehensive program evaluation of the Network. This paper details a formative, process evaluation after approximately 1 year of operations, with the goal of assessing acceptability and feasibility. MethodsUsing a concurrent mixed methods study design, quantitative and qualitative data were simultaneously collected from students in order to evaluate the acceptability and feasibility of the Network as a mental health promotion resource. Quantitative data were automatically collected through Google Analytics via the website over the course of the first year of operations. Data collected included the number of users accessing the website, user engagement, and user “stickiness.” Quantitative data were used to evaluate both accessibility and feasibility. Qualitative data were collected via individual, digital interviews conducted with a modest sample of students (n=8) across areas and levels of study. Qualitative data derived more detailed insights into user experience and website attributes, as well as feedback on content delivery, providing evidence used to evaluate feasibility. ResultsA total of 1200 users globally accessed the Network within the first year of operations, with Canadian users accounting for nearly 90% of total website traffic. An overall 66% engagement rate was observed, with the average user visiting 7 pages per session. Further support for the acceptability of the Network is demonstrated in the Canada-wide reach of the content development and review team. Evidence for the feasibility of the Network was observed through website use statistics indicating the most frequently viewed pages aligned with our goals: providing mental health education and increasing awareness of available resources. Qualitative feedback provided additional context surrounding the feasibility of the space, including positive feedback on the esthetics, relevance, usability, inclusion, and accessibility. Areas for content expansion and improvements to accessibility were also identified. ConclusionsThe results of this study provide evidence in support of the feasibility and acceptability of the Network as a web-based knowledge mobilization initiative in support of postsecondary students’ mental health and well-being. Future research will pursue a summative, impact assessment to evaluate utility.